2021
DOI: 10.1080/03088839.2021.1976430
|View full text |Cite
|
Sign up to set email alerts
|

Articulating intermodal chains through short-sea shipping: a method for assessing the performance of East African ports

Abstract: The location of East African ports, along with difficulties in building and maintaining effective road corridors, has led to the consideration of intermodal transport through Short Sea Shipping (SSS) as an alternative for load transport. However, this potential solution is dependent on the ports as consolidation load centres and on the configuration of transport networks. This paper provides a method to evaluate the performance of East African ports in their role as a hub for the intermodal chain. Specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Several African countries have been making efforts to promote and improve SSS as part of their broader strategies to enhance trade, connectivity, and sustainable transportation. According to [53], the combination of the location of East African ports with the obstacles found in the road corridors of the region, make SSS a consideration for an alternative mode of transportation. In this study, four different ports were identified as suitable locations to implement SSS.…”
Section: Short Sea Shipping Beyond Europe: a Global Perspectivementioning
confidence: 99%
“…Several African countries have been making efforts to promote and improve SSS as part of their broader strategies to enhance trade, connectivity, and sustainable transportation. According to [53], the combination of the location of East African ports with the obstacles found in the road corridors of the region, make SSS a consideration for an alternative mode of transportation. In this study, four different ports were identified as suitable locations to implement SSS.…”
Section: Short Sea Shipping Beyond Europe: a Global Perspectivementioning
confidence: 99%
“…According to formula (10), the comprehensive index value z j (w)(j ∈ N) is According to formula (4), calculate the possibility of comparing the comprehensive index values of port competitiveness, and establish the possibility matrix. 12 i=1 w i = 1, w i ≥ 0, i ∈ (1, 2, 3, ...12) w = (0.08, 0.14, 0.07, 0.1, 0.08, 0.08, 0.08, 0.08, 0.08, 0.07, 0.08, 0.06).…”
Section: Empirical Analysismentioning
confidence: 99%
“…Firstly, from the perspective of port hub competitiveness research, Li et al [1][2][3][4][5][6] carried out research on logistics hub competitiveness at the world level, national level, multimodal transport industry level and port enterprise level, respectively. Forte et al [7][8][9][10] conduct competitiveness research on the dimensions of cost control and economic feasibility for specific multimodal transport markets such as roro market and short-distance marine transport market. Han et al 11,12 studied port competitiveness from the perspective of optimizing the enterprise supply chain.…”
mentioning
confidence: 99%
“…Ports serve as the starting point, transit station, and end point of marine networks, and they are an essential component of transportation networks and economic systems, particularly in international transportation networks. Ports are standard intermodal hubs that dominate the worldwide intermodal wave [9,10]. PCITHs are comprehensive transportation hubs with ports as the core, integrating different modes of transportation, such as sea, land, and air.…”
Section: Introductionmentioning
confidence: 99%